Photodetectors: High‐Gain and Low‐Driving‐Voltage Photodetectors Based on Organolead Triiodide Perovskites (Adv. Mater. 11/2015). (March 2015) - Dong, Rui; Fang, Yanjun; Chae, Jungseok; Dai, Jun; Xiao, Zhengguo; Dong, Qingfeng; Yuan, Yongbo; Centrone, Andrea; Zeng, Xiao Cheng; Huang, Jinsong
Abstract : On page 1912, J. Huang, and co‐workers develop a solution‐processed organolead trihalide perovskite photodetector that combines a high photoconductive gain with a broad spectral response across the ultraviolet (UV) to the near‐infrared (NIR). The hole traps at the top surface of the perovskites are exploited to boost the performance with an ingenious device design at extremely low driving voltage, which enables a compact integration with low‐voltage circuits.